Enhanced Production and Functional Characterization of Recombinant Equine Chorionic Gonadotropin (rec-eCG) in CHO-DG44 Cells - Munkhzaya Byambaragchaa; Sei Hyen Park; Myung-Hum Park; Myung-Hwa Kang; Kwan-Sik Min (Biomolecules, 2025)
Equine chorionic gonadotropin (eCG) hormone, comprising highly glycosylated α- and β-subunits, elicits responses similar to follicle-stimulating hormone (FSH) and luteinizing hormone (LH) in non-equid species. This study aimed to establish a mass production of recombinant eCG (rec-eCG) using CHO DG44 cells. Single-chain rec-eCG β/α was expressed in CHO DG44 cells. FSH- and LH-like activities were evaluated in CHO-K1 and HEK 293 cells expressing the equine LH/CG receptor (eLH/CGR), rat LH/CGR (rLH/CGR), and rFSHR. pERK1/2 activation and β-arrestin 2 recruitment were assessed in PathHunter CHO-K1 cells. The expression from one, among nine isolates, peaked at 364–470 IU/mL on days 9 and 11. The molecular weight of rec-eCG β/α ranged from 40 to 47 kDa, with two distinct bands. PNGase F treatment reduced the molecular weight by 8–10 kDa, indicating N-glycosylation. Rec-eCG β/α demonstrated dose-responsive cAMP activity in cells expressing eLH/CGR, with enhanced potency in rLH/CGR and rFSHR. Phospho-ERK1/2 activation peaked at 5 min before declining rapidly. β-arrestin 2 recruitment was receptor-mediated in cells expressing hFSHR and hLH/CGR. This study provides insights into the mechanisms underlying eCG’s FSH- and LH-like activities. Stable CHO DG44 cells can produce large quantities of rec-eCG. eCG activates pERK1/2 signaling via the PKA/cAMP pathway and facilitates β-arrestin 2 recruitment.